2021
DOI: 10.3390/ijms222111893
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis Inhibition by Hydrogen Sulfide Alleviated Hypoxia-Induced Cardiac Fibroblasts Proliferation via Sirtuin 3

Abstract: Myocardial ischemia or hypoxia can induce myocardial fibroblast proliferation and myocardial fibrosis. Hydrogen sulfide (H2S) is a gasotransmitter with multiple physiological functions. In our present study, primary cardiac fibroblasts were incubated with H2S donor sodium hydrosulfide (NaHS, 50 μM) for 4 h followed by hypoxia stimulation (containing 5% CO2 and 1% O2) for 4 h. Then, the preventive effects on cardiac fibroblast proliferation and the possible mechanisms were investigated. Our results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
(40 reference statements)
2
8
0
Order By: Relevance
“…Actually, a large amount of cellular contents will be released after necroptosis, such as inflammatory factors, cell metabolites, and other substances, which all further promote cell proliferation. Recently, some researchers found that H 2 S attenuated necroptosis depending on sirtuin3 enhancement to suppress excessive proliferation in hypoxia-induced cardiac fibroblasts [ 25 ]. That is to say that the mutual regulation between cell death and proliferation is very complex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, a large amount of cellular contents will be released after necroptosis, such as inflammatory factors, cell metabolites, and other substances, which all further promote cell proliferation. Recently, some researchers found that H 2 S attenuated necroptosis depending on sirtuin3 enhancement to suppress excessive proliferation in hypoxia-induced cardiac fibroblasts [ 25 ]. That is to say that the mutual regulation between cell death and proliferation is very complex.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous H 2 S improved mitochondrial function, inhibited oxidative stress, and reduced necroptosis to improve diabetic cardiomyopathy [ 24 ]. Moreover, H 2 S donors inhibited necroptosis and alleviated hypoxia-induced myocardial fibroblast proliferation depending on sirtuin 3 [ 25 ]. However, whether oxidative stress and necroptosis were involved in the possible effect of H 2 S on skin fibroblast proliferation has not been known well.…”
Section: Introductionmentioning
confidence: 99%
“…Another research verified that exogenous H 2 S supplementation alleviated necroptosis to suppress NLR family pyrin domain‐containing protein 3 (NLRP3) inflammasome activation and attenuate diabetic cardiomyopathy via mitochondrial dysfunction improvement and oxidative stress inhibition 30 . H 2 S also inhibited oxidative stress‐induced necroptosis and attenuated cardiac fibroblast proliferation during hypoxia 35 . Our latest research confirmed that H 2 S inhibited the proliferation of human keloid skin fibroblasts by relieving oxidative stress and necroptosis 14 .…”
Section: Discussionmentioning
confidence: 54%
“…30 H 2 S also inhibited oxidative stress-induced necroptosis and attenuated cardiac fibroblast proliferation during hypoxia. 35 Our latest research confirmed that H 2 S inhibited the proliferation of human keloid skin fibroblasts by relieving oxidative stress and necroptosis. 14 From two opposite perspectives of endogenous H 2 S disturbance and exogenous H 2 S supplement, the current research proved eloquently that H 2 S was an endogenous protective factor to alleviate oxidative stress and necroptosis, and further to inhibit excessive proliferation of skin fibroblasts.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation